2016
DOI: 10.3389/fnins.2016.00238
|View full text |Cite
|
Sign up to set email alerts
|

Functional Zonation of the Adult Mammalian Adrenal Cortex

Abstract: The standard model of adrenocortical zonation holds that the three main zones, glomerulosa, fasciculata, and reticularis each have a distinct function, producing mineralocorticoids (in fact just aldosterone), glucocorticoids, and androgens respectively. Moreover, each zone has its specific mechanism of regulation, though ACTH has actions throughout. Finally, the cells of the cortex originate from a stem cell population in the outer cortex or capsule, and migrate centripetally, changing their phenotype as they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 285 publications
(290 reference statements)
1
39
0
1
Order By: Relevance
“…Nevertheless, evidence from animal studies favors the progenitor cell proliferation/migration hypothesis [7]. This theory proposes that the cortical cells originate from a stem cell population in the outer cortex or capsule, and migrate centripetally becoming functionally differentiated in the appropriate zonal environment [1, 5, 7]. In agreement with the migration model, the cell proliferation index is highest in the outer ZG of human adrenal tissues from early infancy to late puberty [8].…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Nevertheless, evidence from animal studies favors the progenitor cell proliferation/migration hypothesis [7]. This theory proposes that the cortical cells originate from a stem cell population in the outer cortex or capsule, and migrate centripetally becoming functionally differentiated in the appropriate zonal environment [1, 5, 7]. In agreement with the migration model, the cell proliferation index is highest in the outer ZG of human adrenal tissues from early infancy to late puberty [8].…”
Section: Introductionsupporting
confidence: 48%
“…The origin and maintenance of the adrenocortical zones have been debated over the years. Nevertheless, evidence from animal studies favors the progenitor cell proliferation/migration hypothesis [7]. This theory proposes that the cortical cells originate from a stem cell population in the outer cortex or capsule, and migrate centripetally becoming functionally differentiated in the appropriate zonal environment [1, 5, 7].…”
Section: Introductionmentioning
confidence: 99%
“…A close morphological and functional interdependence of cortical and chromaffin cells has already been demonstrated (reviewed in (Ehrhart- Bornstein and Bornstein, 2008)). In fact, it becomes more and more clear that the functions of the adrenal gland should be viewed more as an integrated whole greater than the sum of its parts (Haase et al, 2011;Vinson, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This idea was first hypothesized in the 19th century, based on histological observations of gradual changes in morphology observed in cells between the capsule and the medulla (32, 33) [reviewed in Ref (34)]. Over the years, different studies have shown that, under physiological conditions, proliferating cells are located preferentially in the outermost layers of the cortex, in the subcapsular region (35, 36).…”
Section: Progenitor Populations In the Adrenal Glandmentioning
confidence: 99%